PENGARUH PUPUK ORGANIK TERHADAP PERTUMBUHAN SENGON (Albizia falcataria (L.) Fosberg) - Muswita, Muswita; Murni, Pinta; Herliana, Lia (Universitas Jambi, 2008)
The research has objectives to know the effect of kind of organic manure to growth and know optimal kind ofmanure to growth sengon (Albizia falcataria(L.) Fosberg). This research used completely randomize designconsisted of 5 treatment such as goats manure, chickens manure, cows manure, compost manure andwithout manure with 5 replication. The data dianalysed with Anova and test continue DNMRT at 5% reallevel. The result showed that organic manure was significantly different to high and sengon stem diameter butwas not significantly differen to amount of leaf. Based of the result of research , it may be concleted thatgoats manure gave the best result.